His Bundle Pacing and Left Bundle Branch Pacing in Patients with Heart Failure - Patrycja Paluszkiewicz; Adrian Martuszewski; Jadwiga Radziejewska; Jacek Zawadzki; Jacek Smereka; Jacek Gajek (Biomedicines, 2024)
Background: His bundle pacing (HBP) and left bundle branch pacing (LBBP) are emerging therapies for patients with heart failure and conduction disorders, offering potential advantages over traditional pacing methods. These approaches aim to restore physiological conduction and improve cardiac function more effectively. Objective: This study aims to evaluate the efficacy and safety of HBP and LBBP in patients with heart failure and conduction disturbances, comparing these techniques to conventional pacing. Methods: A comprehensive review of recent studies and clinical trials was conducted, focusing on the performance of HBP and LBBP in improving cardiac function, reducing QRS duration, and enhancing overall patient outcomes. The analysis includes data on clinical efficacy, procedural safety, and long-term benefits associated with these pacing modalities. Results: Both HBP and LBBP have demonstrated significant improvements in cardiac function and clinical outcomes compared to conventional pacing. HBP effectively restores physiological conduction with improved synchronization and a reduction in QRS duration. LBBP has shown enhanced left ventricular activation, leading to better overall cardiac performance. Both techniques have been associated with a lower incidence of complications and a higher success rate in achieving optimal pacing thresholds. Conclusions: HBP and LBBP offer promising alternatives to traditional pacing for patients with heart failure and conduction disorders. These advanced pacing strategies provide superior clinical outcomes and improved cardiac function with reduced risk of complications. Further research and clinical trials are needed to fully establish the long-term benefits and safety profiles of these techniques in diverse patient populations.